2013
DOI: 10.1111/bcp.12097
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide receptors as potential drug targets in the treatment of inflammatory conditions

Abstract: Cross-talk between the nervous, endocrine and immune systems exists via regulator molecules, such as neuropeptides, hormones and cytokines. A number of neuropeptides have been implicated in the genesis of inflammation, such as tachykinins and calcitonin gene-related peptide. Development of their receptor antagonists could be a promising approach to anti-inflammatory pharmacotherapy. Anti-inflammatory neuropeptides, such as vasoactive intestinal peptide, pituitary adenylate cyclase-activating polypeptide, a-mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 171 publications
(223 reference statements)
1
45
0
Order By: Relevance
“…The physiological relevance of up-regulating neuropeptides by a TNF-to-IL6 cascade may be related to their involvement in steroidogenesis in the adjacent adrenal cortex, with initiation by TNFa, and then IL6, allowing cytokine inflammatory effects occurring systemically to be temporally limited by a linked but delayed anti-inflammatory response. Such a mechanism might serve to optimize the antiseptic actions of TNFa, while minimizing damage to the host during sepsis (Mazzocchi et al 1992Andreis et al 2007;Belloni et al 2007;Kormos and Gaszner 2013;Pinter et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological relevance of up-regulating neuropeptides by a TNF-to-IL6 cascade may be related to their involvement in steroidogenesis in the adjacent adrenal cortex, with initiation by TNFa, and then IL6, allowing cytokine inflammatory effects occurring systemically to be temporally limited by a linked but delayed anti-inflammatory response. Such a mechanism might serve to optimize the antiseptic actions of TNFa, while minimizing damage to the host during sepsis (Mazzocchi et al 1992Andreis et al 2007;Belloni et al 2007;Kormos and Gaszner 2013;Pinter et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Discussing the divergent effects of all neuropeptides goes beyond the scope of this review. Selective modulation of their receptors could provide a novel approach in analgesic and anti‐inflammatory drug development …”
Section: Novel Targets With Anti‐inflammatory And/or Analgesic Potentmentioning
confidence: 99%
“…These do not only mediate pain but also local neurogenic inflammatory reaction via the release of vasoactive, proinflammatory neuropeptides such as tachykinins [e.g., substance P (SP)], calcitonin gene‐related peptide (CGRP), vasoactive intestinal polypeptide (VIP), and pituitary adenylate‐cyclase activating polypeptide (PACAP). Meanwhile, inhibitory neuropeptides (somatostatin, opioid peptides) are also simultaneously released from these nerve terminals that limit inflammation and pain locally and also via the systemic circulation . These nerve endings are activated/sensitized by a variety of different mediators produced during inflammation, such as protons, hydrogen peroxide, formaldehyde, prostaglandins (PGs), and leukotrienes.…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte infiltration in the brain boosts inflammatory activation of various cells such as microglia and astrocytes [72]. Recent studies have explored the ability of neuropeptides with physiological functions such as galanin peptides, to prevent and alleviate poststroke inflammatory responses [7374]. Several studies have demonstrated that upregulation of GalR1 is related to the increased expression of nuclear factor (NF)-κB, which is an inflammatory signaling molecule in inflammatory animal models [7576].…”
Section: Galanin In Post-stroke Inflammationmentioning
confidence: 99%